1984
DOI: 10.1128/aem.47.5.889-894.1984
|View full text |Cite
|
Sign up to set email alerts
|

Novel method for studying the public health significance of macroinvertebrates occurring in potable water

Abstract: An experimental procedure was developed to study the association of selected bacteria and macroinvertebrates and their response to free available chlorine disinfection. The organisms selected for study were Escherichia coli (LacZ545), Enterobacter cloacae (ATCC 23355), and the amphipod Hyalella azteca. E. coli was shown to bind tightly (1.6 x 104 CFU per amphipod) to this macroinvertebrate and to resist repeated attempts to wash it off. E. cloacae was shown to bind much less tightly (1.4 x 103 CFU per amphipod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Research has shown that increased resistance to disinfection results from attachment or association of microorganisms to various surfaces, including macroinvertebrates (Crustacea, Nematoda, Platyhelminthes, and Insecta) (31,53), turbidity particles (19-22, 27, 46), algae (51), carbon fines (7, 28), and even glass microscope slides (43), provides increased resistance to disinfection. Ridgway and Olson (46) showed that the majority of viable bacteria in chlorinated drinking water were attached to particles.…”
mentioning
confidence: 99%
“…Research has shown that increased resistance to disinfection results from attachment or association of microorganisms to various surfaces, including macroinvertebrates (Crustacea, Nematoda, Platyhelminthes, and Insecta) (31,53), turbidity particles (19-22, 27, 46), algae (51), carbon fines (7, 28), and even glass microscope slides (43), provides increased resistance to disinfection. Ridgway and Olson (46) showed that the majority of viable bacteria in chlorinated drinking water were attached to particles.…”
mentioning
confidence: 99%
“…Available research has shown that increased resistance to disinfection may result from the attachment of microorganisms to or the association of microorganisms with various surfaces, including macroinvertebrates (Crustacea, Nematoda, Platyhelminthes, and Insecta) (26,36), turbidity particles (17-19, 23, 31), algae (34), carbon fines (7,24), and even glass microscope slides (29). Ridgway and Olson (31) have shown that the majority of viable bacteria in chlorinated drinking water are attached to particles.…”
mentioning
confidence: 99%
“…Moreover, many bacteria can survive and multiply within the intracellular environment of eukaryotic cells, an ecosystem that provides protection against hostile environmental conditions (e.g. disinfectants) as well as nutrients for growth (Levy et al. 1984; Barbaree et al.…”
Section: Introductionmentioning
confidence: 99%